Taurine Protects C2C12 Myoblasts From Impaired Cell Proliferation and Myotube Differentiation Under Cisplatin-Induced ROS Exposure - Zhou, Lin; Lu, Ruohan; Huang, Caihua; Lin, Donghai (Frontiers in Molecular Biosciences, 2021)
In cancer patients, chemotherapeutic medication induces aberrant ROS (reactive oxygen species) accumulation in skeletal muscles, resulting in myofiber degradation, muscle weakness, and even cachexia, which further leads to poor therapeutic outcomes. Acting as an antioxidant, taurine is extensively used to accelerate post-exercise muscle recovery for athletes. The antioxidant effects of taurine have been shown in mature myotubes and myofibers but not yet in myoblasts, the myotube precursor. The proliferation and differentiation abilities of myoblasts is a decisive motivity in myofiber repair and regeneration, which is usually impaired during chemotherapeutics in cancer patients as well. Here we explored the effects of taurine supplementation on C2C12 myoblasts exposed to cisplatin-induced ROS. We found that cisplatin treatment led to dramatically decreased cell viability, accumulated ROS level, down-regulated expressions of MyoD1 (myoblast determination protein 1) and myogenin, MHC (myosin heavy chain) and impaired myotube differentiation in myoblasts. Significantly, taurine supplementation protected myoblasts against cisplatin-induced cell viability decrease, promoted cellular ROS clearance, and most importantly, preserved the expressions of MyoD1, myogenin and MHC as well as myotube differentiation ability. We further conducted NMR-based metabolomic analysis to clarify the underlying molecular mechanisms. We identified 14 characteristic metabolites primarily responsible for the discrimination of metabolic profiles between cisplatin-treated cells and normal counterparts, including increased levels of BCAAs (branched-chain amino acids: leucine, isoleucine), alanine, glycine, threonine, glucose, ADP (adenosine diphosphate), phenylalanine and PC (O-phosphocholine), decreased levels of lysine, β-alanine, choline, GPC (sn-glycero-3-phosphocholine) and myo-inositol. Evidently, taurine supplementation partially reversed the changing trends of several metabolites (isoleucine, threonine, glycine, PC, β-alanine, lysine, myo-inositol). Furthermore, taurine supplementation promoted the proliferation and myotube differentiation of myoblasts through alleviating cellular catabolism, facilitating GSH (reduced glutathione) biosynthesis, improving glucose utilization and TCA (tricarboxylic acid) cycle anaplerosis, and stabilizing cellular membranes. Our results demonstrated the protective effects of taurine on cisplatin-impaired myoblasts, and elucidated the mechanistic rationale for the use of taurine to ameliorate muscle toxicity in clinical chemotherapy cancer patients.